Freshwater biodiversity in a rapidly changing Arctic: An expert horizon scan of key research questions - Joseph M. Culp; Michael Power; Kirsten S. Christoffersen; Willem Goedkoop; Kimmo K. Kahilainen; Milla Rautio; Fernando Chaguaceda; Marie-Pier Hébert; Sanne M. Moedt; Dermot Antoniades; Simon Belle; Daniel Bolnick; et al. (Ambio, 2026)
Arctic freshwater biodiversity is rapidly changing due to climate warming, resource extraction, infrastructure development, and landscape transformation. To improve understanding, predict future responses, and inform policy formulation, research needs must be clearly identified. Using a horizon scan survey, Arctic freshwater experts from government, international agencies, and Indigenous Peoples identified 77 biodiversity research questions with 17 highlighted as most important for near term assessment. These questions span nine thematic categories: biodiversity and taxonomic challenges, hydrological change, productivity and food webs, ecosystem connectivity, methods, monitoring and assessment, permafrost change, winter ecology, anthropogenic development, and Indigenous Knowledge. Climate change emerged as the major driver among all categories and research questions. A key priority identified was the urgent need for long-term, harmonized monitoring programs among Arctic countries. Multiple knowledge gaps detected suggest that circumpolar research collaborations are required to tackle these issues.

eDNA2IQI: an eDNA/random forest-based prediction tool that accurately predicts ecological status for regulatory-compliance assessment - A.J. Wyness; T. Stoeck; B.J. Morrissey; I. Berrill; K. Davidson; C. FairBairn; S. MacIntyre; C. Webb; T. Foster; S. Brain; D. Svobodova; C. Clark; et al. (Aquaculture, 2026)

Using Nearshore Fish Communities to Evaluate Eutrophication Impact in Temperate Estuaries - Mark D. Saunders; Nathanael Bergbusch; Kyle M. Knysh; Leah P. MacIntyre; Christina C. Pater; Michael R. S. Coffin; Monica Boudreau; Michael R. van den Heuvel; Simon C. Courtenay (Fishes, 2025)
Using fishes as indicators of estuarine degradation is informative in long-term monitoring programs. Beach seine hauls were used in four estuaries that differed in their trophic and tidal status. The study found that inner, middle, and outer estuarine nearshore fish communities differed significantly at from all estuaries, for all sampling times. To reduce the effects of within-estuary variability, between-estuary differences were examined separately for inner, middle, and outer estuarine areas. These analyses revealed differences in north-south and trophic status in communities between estuaries. The north-south differences were characterized by more benthic fishes, such as mummichogs and fourspine stickleback in the microtidal northern estuaries and proportionally more pelagic fishes, such as Atlantic silversides and river herring in the mesotidal estuaries. In both multivariate and univariate analyses, mummichogs were also featured as being most abundant in the more eutrophic estuaries. The distance-based redundancy analysis showed that bare sediment coverage was the strongest correlate of the north-south differences, while the Ulva to Zostera plant gradient was more influential in predicting eutrophication impacts on communities in the inner and middle estuary.

Investigating the role of allelochemicals in the interaction between Alexandrium monilatum and other phytoplankton species - Sylvain Gaillard; Hamish J. Small; Nour Ayache; Simon Tanniou; Philipp Hess; Damien Réveillon; Constance M. Harris; Thomas M. Harris; Gail P. Scott; Alanna MacIntyre; Kimberly S. Reece (Harmful Algae, 2024)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Greenhouse gas emission and storage in a small shallow lake - M. Bartosiewicz; I. Laurion; S. MacIntyre (Hydrobiologia, 2015)

Percutaneous image-guided biopsy of prostate cancer metastases yields samples suitable for genomics and personalised oncology - Matthew K. H. Hong; Nikhil Sapre; Pramit M. Phal; Geoff Macintyre; Xiaowen Chin; John S. Pedersen; Andrew Ryan; Michael Kerger; Anthony J. Costello; Niall M. Corcoran; Christopher M. Hovens (Clinical & Experimental Metastasis, 2014)

Spatial variability of nutrient concentrations, fluxes, and ecosystem metabolism in Nyanza Gulf and Rusinga Channel, Lake Victoria (East Africa) - P. Gikuma-Njuru; R. E. Hecky; S. J. Guildford; S. MacIntyre (Limnology and Oceanography, 2013)
Measurements of nutrient concentrations and physicochemical parameters were carried out monthly between March 2005 and March 2006 along a transect between the Nyanza Gulf and the open waters of Lake Victoria to evaluate spatial and seasonal variations in nutrient fluxes and ecosystem metabolism. Nutrient concentration gradients were observed between the deep and seasonally stratifying main lake basin and the large, shallow river‐influenced Nyanza Gulf, which are connected by the relatively deep and narrow Rusinga Channel. Nutrient gradients were steepest in the Rusinga Channel where there was always a strong gradient in electrical conductivity. A mixing‐box model used to quantify nutrient fluxes and ecosystem metabolism along the gulf and the channel showed that nutrients entering the gulf through river inflows and municipal sources were largely retained in the gulf, with only a small fraction transferred into the main lake. In contrast, the main lake was a net exporter of dissolved inorganic phosphorus to the gulf (110 mg P m −2 yr −1 ), which is in contrast to the paradigm that the gulf is a major contributor to the increasing nutrient enrichment and, hence, eutrophication of the greater Lake Victoria. The channel had net regeneration of dissolved nutrients indicating net heterotrophy; whereas in the gulf, there was net consumption of dissolved nutrients, resulting in high estimates of net ecosystem production (570 mg C m −2 d −1 ) and, hence, net autotrophy. Nitrogen balance ranged from +3 to +15 mg N m −2 d −1 , indicating dominance of nitrogen fixation over denitrification in both the gulf and the channel, which are both well‐oxygenated.

Modeling lakes and reservoirs in the climate system - M. D. MacKay; P. J. Neale; C. D. Arp; L. N. De Senerpont Domis; X. Fang; G. Gal; K. D. Jöhnk; G. Kirillin; J. D. Lenters; E. Litchman; S. MacIntyre; P. Marsh; et al. (Limnology and Oceanography, 2009)
Modeling studies examining the effect of lakes on regional and global climate, as well as studies on the influence of climate variability and change on aquatic ecosystems, are surveyed. Fully coupled atmosphere‐land surface‐lake climate models that could be used for both of these types of study simultaneously do not presently exist, though there are many applications that would benefit from such models. It is argued here that current understanding of physical and biogeochemical processes in freshwater systems is sufficient to begin to construct such models, and a path forward is proposed. The largest impediment to fully representing lakes in the climate system lies in the handling of lakes that are too small to be explicitly resolved by the climate model, and that make up the majority of the lake‐covered area at the resolutions currently used by global and regional climate models. Ongoing development within the hydrological sciences community and continual improvements in model resolution should help ameliorate this issue.

The impact of scallop drags on sea urchin populations and benthos in the Bay of Fundy, Canada - S.M.C. Robinson; S. Bernier; A. MacIntyre (Hydrobiologia, 2001)

A classic Caribbean algal ridge, Holandés Cays, Panamá: an algal coated storm deposit - Ian G. Macintyre; Peter W. Glynn; Robert S. Steneck (Coral Reefs, 2001)

Role of the melanocortin-4 receptor in metabolic rate and food intake in mice - Airu S. Chen; Joseph M. Metzger; Myrna E. Trumbauer; Xiao-ming Guan; Hong Yu; Easter G. Frazier; Donald J. Marsh; Michael J. Forrest; Shobhna Gopal-Truter; Jill Fisher; Ramon E. Camacho; Alison M. Strack; et al. (Transgenic Research, 2000)

Ecological controls on stromatolite development in a modern reef environment: A test of the ecological refuge paradigm - R. S. Steneck; T. E. Miller; R. P. Reid; I. G. Macintyre (Carbonates and Evaporites, 1998)

A unique algal ridge system in the Exuma Cays, Bahamas - R. S. Steneck; I. G. Macintyre; R. P. Reid (Coral Reefs, 1997)